Impact of Technology Use on Behavior and Sleep Scores in Preschool Children in Saudi Arabia - Almuaigel, Doaa; Alanazi, Abrar; Almuaigel, Mohammed; Alshamrani, Foziah; AlSheikh, Mona; Almuhana, Nora; Zeeshan, Mohammad; Alshurem, Mohammed; Alshammari, Alaa; Mansi, Kamel (Frontiers in Psychiatry, 2021)
Background: Pre-school children use digital devices both at home and in kindergarten for communication. However, such technologies can also be used for creativity learning and entertainment. Technology usage might exert a negative impact on the psychosocial development of pre-school children, thus necessitating parental monitoring. Previous studies have recommended early intervention for pre-school children by decreasing the duration of digital devices, spending more time with the family, and participation in motor activities to avoid the ill effects of technology. Aim: To investigate the impact of digital device use on the behavioral and sleep scores of preschool children as perceived by parents in Saudi Arabia (SA). Method: This cross-sectional study was conducted across two regions in SA. It was ethically approved by the ethical review board of Imam Abdulrahman Bin Faisal University. The participants were randomly selected from well-baby hospital records, surveyed and interviewed to obtain data for the following measures: demographic data, technology usage, sleep disturbance scale, and behavior scale. Children with special needs or comorbidities were excluded from the study. Descriptive and multivariate regression analysis were done. Results: We recruited 288 children. Most did not attend schools (63.2%), 22.6% were in kindergarten, and 14.2% were in nursery schools. Smart phones were the most commonly used device by the children (42.4%). Most used the technology for 2–3 h/days (34%). Cartoons were the most commonly sought content (42%). The behavior scores for children aged 18–36 months showed a mean value of 5.1, 3.7, and 4.6 for surgency, negative affect, and effortful control, respectively. Children aged 3–5 years showed a mean value of 4.3, 4, and 4.7 for surgency, negative affect, and effortful control, respectively. Sleep disturbance scores for all children showed a mean value of 12.4, 3.5, 3.8, 8, 7.3, and 2.7 on disorders of initiating and maintaining sleep, sleep-breathing disorders, disorders of arousal, sleep-wake transition disorders, disorders of excessive somnolence, and sleep hyperhidrosis, respectively. The mean total sleep score was 37. Multivariate regression analysis showed significant positive relationship between surgency and three factors namely family income of 10,000–15,000 SR (t = 1.924, p = 0.045), fathers' bachelor's degrees (t = 2.416, p = 0.16), and owning a video game device (t = 2.826, p = 0.005<0.05). Negative affect was significantly associated with fathers' diploma level of education (t = 2.042, p = 0.042). Negative significant relationship between effortful control and fathers' secondary level of education (t = −2.053, p = 0.041). There was a significant negative relationship between effortful control and owning a TV and video game device (t = −2.35, −2.855, p = 0.043, 0.005<0.05, respectively). A significant positive relationship was found between child's sleeping score (worse sleep) and watching technology between 3 and 5 h (t = 2.01, p = 0.045), and mothers' unemployment status (t = 2.468, p = 0.014). Conclusion: In conclusion, technology use is associated with a negative impact on children sleep and behavior. Owning a digital device, using tablets, screen viewing for more than 3–5 h, and watching movies were significantly associated with negative child's behavior and sleep.